1988
DOI: 10.1111/j.1476-5381.1988.tb11399.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between atria from control and streptozotocin‐diabetic rats: The effects of dietary myoinositol

Abstract: 1 Atria, isolated from control rats, six-week streptozotocin-diabetic rats and from similarly diabetic rats treated with myo-inositol (MI) were compared. The MI treatment was shown to reverse the depressed sciatic nerve MI which was observed in the untreated diabetic group. 2 Spontaneously beating atria from the untreated diabetic animals beat more slowly, and with greater force than tissues from the control group. When electrically driven at 4 Hz they were found to be less sensitive to the negative inotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 20 publications
4
19
0
1
Order By: Relevance
“…Although reduced heart rate variability, a feature of SND, could be due to intrinsic SAN defects, loss of normal autonomic function, or a combination of both, our ex vivo findings indicate that STZ treatment directly affects SAN, causing intrinsic SND by increased apoptosis, fibrosis, and subsequent electrical source-sink mismatch between SAN and myocardium. Our findings do not dispute a role for autonomic dysfunction in diabetes-induced defects in heart rate but appear consistent with other evidence showing diabetes causes pathological effects on SAN (44)(45)(46).…”
Section: Discussionsupporting
confidence: 79%
“…Although reduced heart rate variability, a feature of SND, could be due to intrinsic SAN defects, loss of normal autonomic function, or a combination of both, our ex vivo findings indicate that STZ treatment directly affects SAN, causing intrinsic SND by increased apoptosis, fibrosis, and subsequent electrical source-sink mismatch between SAN and myocardium. Our findings do not dispute a role for autonomic dysfunction in diabetes-induced defects in heart rate but appear consistent with other evidence showing diabetes causes pathological effects on SAN (44)(45)(46).…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings have been reported for diabetic (Pfaffman, 1980;Kofo-Abayomi & Lucas, 1988), but not galactosaemic rats. Action potentials and repolarization are prolonged in diabetic atria.…”
Section: Discussionsupporting
confidence: 78%
“…Contraction in papillary muscles and atria were examined. There have not been any reports on atrial contractile properties in diabetes, although some dysfunction was expected because resting beat rate is reduced, and sensitivity to autonomic agents is changed (Foy & Lucas, 1978;Tomlinson & Yusof, 1983;Kofo-Abayomi & Lucas, 1988 (Special Diet Services, Manea, Cambs). A third group of normal onset controls was also used; previous studies have shown that their contractile properties do not differ from those of age-matched control rats ).…”
Section: Introductionmentioning
confidence: 99%
“…Defective Ca 2+ signalling mechanisms, including reductions in L‐type Ca 2+ channel current, depressed sarcoplasmic reticulum Ca 2+ uptake and release mechanisms, and reduced rate of Ca 2+ efflux on the Na + –Ca 2+ exchange, partly underlie these contractile defects (Lagadic‐Gossmann et al 1996; Chattou et al 1999; Choi et al 2002). Reductions in heart rate (HR) in isolated perfused heart (Li et al 1989; Nicholl et al 1991; Imai et al 1991; Ravingerova et al 1996; De Angelis et al 2000; Nemeth et al 2001) and spontaneous beating rate in right atria (Goyal & McNeill, 1985; Ramanadham & Tenner, 1986; Kofo‐Abayomi & Lucas, 1988; Nagamine et al 1989; Booth & Hodgson, 1993; Hicks et al 1997; Sellers & Chess‐Williams, 2000) from STZ‐treated rats suggest that intrinsic defects are partly responsible for heart rhythm disturbances. In vivo studies have also demonstrated reduced HR and reductions in heart rate variability (HRV), suggesting that extrinsic control of heart rhythmicity may also be defective in STZ‐treated rats (Hicks et al 1998; Fazan et al 1999; Lo et al 2002; Howarth et al 2005).…”
mentioning
confidence: 99%